me ajudem pfv,agradeço se puder

Resposta:
4.
A) [tex]4^{13}[/tex]
B) [tex]4^{-5}[/tex]
C) [tex]2^{12}[/tex]
D) [tex]6^}[/tex]
E) [tex]9^{2}[/tex]
Explicação passo-a-passo:
a) 4([tex]^{(-3)[/tex]²) + 4 =
[tex]4^{9+4[/tex] =
= [tex]4^{13}[/tex]
b) [tex]4^{-3}[/tex] elevado a 2 + 4 =
[tex]4^{-9}^{+4}[/tex] =
= [tex]4^{-5}[/tex]
c) [tex]2^{-20}[/tex] ÷ [tex]2^{-32}[/tex] =
= [tex]2^{12}[/tex]
d) [tex]6^{-8}[/tex] ÷ [tex]6^{-9}[/tex] =
[tex]6^{-8 + 9}[/tex] =
= [tex]6^{1}[/tex]
e) [tex]9^{-2x(-1)}[/tex] (qualquer termo multiplicado por -1 resulta no seu oposto)
[tex]9^{2}[/tex]